Achieving Sustainable Business Excellence The Role of Human Capital - Lasrado, Flevy (Springer International Publishing, 2018)
Compiling the best practices of business excellence frameworks around the world, this new book addresses the need for innovative research on sustainable business performance. Using detailed empirical studies, the authors outline the motives and benefits of the implementation of such frameworks in different geographical regions. Comprehensive case studies showcase how the variety of excellence frameworks are manifested in their work cultures, values and beliefs. Academics studying quality management, HRM, and international business will find this book an essential read as it establishes the relevance of human capital in achieving and sustaining global business excellence.